The protectionist threat to world trade relations - Olivier Long (Intereconomics, 1977)
In view of the lasting recession and the constantly high numbers of unemployed in the western industrialised countries, endangered industries and some governments resorted to protectionism during the last months. Besides Olivier Long, Director General of GATT, Wilhelm Haferkamp, Vice-President of the EC Commission, and Otto Wolff von Amerongen, President of the Central Association of German Chambers of Industry and Commerce, in the following two contributions pronounce on the inherent risks to free trade and our prosperity.
Keywords: 330; Trade